O papel das finanças públicas na efetivação dos direitos fundamentais - Alcântara, Michele Alencar da Cruz (2007)
In the present work, it is analyzed constitutional interface between the public finances and the fundamental rights. Related interface it is found through the principles and objectives constitutional. The function of the public finances in the fulfilment of the fundamental rights can be evidenced, as soon as the tributes must be created and be collected in observance to the fundamental rights and with sights to take care of to the necessities human beings. On the other hand, the public expenditures must be elaborated and be applied in order to take care of to the necessities human beings, protecting the constitutional minimum to make face to the costs of the fundamental rights. However, in Brazil, the crisis in the public finances and the mitigation of the fundamental rights has wronged the performance of this function. It is necessary, therefore, to define the protagonists of the function of the public finances in the fulfillment of the fundamental rights, to let them conscious on the rights and duties. It is still essential to demonstrate the dimensions in which the main function of the public finances and the concretion of the fundamental rights can be exerted. These dimensions that are equivalent to the division of functions of the State Power, which if calls of politics, normative and judicial. They coexist in a harmonious way and they can intervene one on the other, so that the function of the public finances in the fulfilment of the fundamental rights is carried out.